Engineering water dissociation sites in MoS2 nanosheets for accelerated electrocatalytic hydrogen production - Zhang, Jian; Wang, Tao; Liu, Pan; Liu, Shaohua; Dong, Renhao; Zhuang, Xiaodong; Chen, Mingwei; Feng, Xinliang (Energy & Environmental Science, 2016)
Earth-abundant MoS2 is widely reported as a promising HER electrocatalyst in acidic solutions, but it exhibits extremely poor HER activities in alkaline media due to the slow water dissociation process. Here we present a combined theoretical and experimental approach to improve the sluggish HER kinetics of MoS2 electrocatalysts through engineering the water dissociation sites by doping Ni atoms into MoS2 nanosheets. The Ni sites thus introduced can effectively reduce the kinetic energy barrier of the initial water-dissociation step and facilitate the desorption of the -OH that are formed. As a result, the developed Ni-doped MoS2 nanosheets (Ni-MoS2) show an extremely low HER overpotential of similar to 98 mV at 10 mA cm-2 in 1 M KOH aqueous solution, which is superior to those (>220 mV at 10 mA cm-2) of reported MoS2 electrocatalysts.